KOMUNIKASI KELOMPOK TERHADAP PERILAKU KONSUMTIF PADA KOMUNITAS HELM BTS (BIKER TEAM SUNMORI) DI KOTA BOGOR - Ernawati , Erna; Saspira, Ratih (Fakultas Ilmu Dakwah dan Komunikasi, 2022)
The Helmet Community is a form of group communication that is formed due to a common interest in something, especially Helmets. This study aims to test whether there is consumptive behavior in the BTS Helmet Community (Biker Team Sunmori) in Bogor City. This study applied a quantitative approach and the sample consisted of 22 respondents who are members of the BTS helmet community (Biker Team Sunmori). Saturated sampling was used in this study, meaning that the entire population was used as the research sample. Observation and data collection techniques using quantitative methods. IBM SPSS Statistics 26.0 for Windows software is used to process data that meets the criteria of validity and simple regression tests. The results of the statistical assessment can be seen that there is an influence between the independent variable group communication on the dependent variable Consumptive Behavior. Based on the calculation of the determinant coefficient, it is known that the group communication variable is 0.18 or 18%, while the remaining 82% of other variables are not examined in this study. Therefore, this research proves that group communication has a positive effect but the status is not strong (weak) on consumptive behavior in the BTS (Biker Team Sunmori) community in Bogor City.